Estimates of Horizontal Groundwater Flow Velocities in Boreholes. Issue 4 (19th September 2018) - Bayer‐Raich, Martí; Credoz, Anthony; Guimerà, Jordi; Jordana, Salvador; Sampietro, Diego; Font‐Capó, Jordi; Nief, Nathalie; Grossemy, Matthieu
Abstract: Currently, monitoring tools can be deployed in observation boreholes to better assess groundwater flow, flux of dissolved contaminants and their mass discharge in an aquifer. The relationship between horizontal water velocity in observation boreholes and Darcy fluxes in the surrounding aquifer has been studied for natural flow conditions (i.e., no pumping). Interpretation of measurements taken with dilution tests, the colloidal borescope, the Heat Pulse Flowmeter, and other techniques require the conversion of observed borehole velocity u to aquifer Darcy flux q ∞ . This conversion is typically done through a proportionality factor α  =  u / q ∞ . In experimental studies as well as in theoretical developments, reported values of α vary almost three orders of magnitude (from 0.5 to 10). This large variability in reported values of α could be explained by: (1) unclear distinction between Darcy flux and water seepage velocity, (2) unclear definition of water velocity in the borehole, (3) effects of well screen and the presence of the measurement device itself on the observable velocities, and (4) hydraulic conditions in the borehole annulus. We address (1), (2) from a conceptual/theoretical perspective, and (3) by means of numerical simulations. We show that issue (1) in low porosity aquifers can yield to order‐of‐magnitude discrepancies in estimates of q ∞ ; (2) may result in discrepancies of up to 50%, and (3) can cause differences up to 20% of water velocity in the borehole void space compared to the theoretical case of an open borehole. Abstract : Article impact statement : Observed horizontal velocity within a borehole vs. actual Darcy flux in the aquifer: how to transform the first to the second.